Disparities in Antihypertensive Prescribing After Stroke: Linked Data From the Australian Stroke Clinical Registry. Issue 12 (December 2019) - Dalli, Lachlan L.; Kim, Joosup; Thrift, Amanda G.; Andrew, Nadine E.; Lannin, Natasha A.; Anderson, Craig S.; Grimley, Rohan; Katzenellenbogen, Judith M.; Boyd, James; Lindley, Richard I.; Pollack, Michael; Jude, Martin; et al.
Abstract : Background and Purpose—: Despite evidence to support the prescription of antihypertensive medications before hospital discharge to promote medication adherence and prevent recurrent events, many patients with stroke miss out on these medications at discharge. We aimed to examine patient, clinical, and system-level differences in the prescription of antihypertensive medications at hospital discharge after stroke. Methods—: Adults with acute ischemic stroke or intracerebral hemorrhage alive at discharge were included (years 2009–2013) from 39 hospitals participating in the Australian Stroke Clinical Registry. Patient comorbidities were identified using the International Statistical Classification of Diseases and Related Health Problems (Tenth Edition, Australian Modification ) codes from the hospital admissions and emergency presentation data. The outcome variable and other system factors were derived from the Australian Stroke Clinical Registry dataset. Multivariable, multilevel logistic regression was used to examine factors associated with the prescription of antihypertensive medications at hospital discharge. Results—: Of the 10 315 patients included, 79.0% (intracerebral hemorrhage, 74.1%; acute ischemic stroke, 79.8%) were prescribed antihypertensive medications at discharge. Prescription varied between hospital sites, with 6 sites >2 SDs below the national average for provision of antihypertensives at discharge. Prescription was also independently associated with patient and clinical factors including history of hypertension, diabetes mellitus, management in an acute stroke unit, and discharge to rehabilitation. In patients with acute ischemic stroke, females (odds ratio, 0.85; 95% CI, 0.76–0.94), those who had greater stroke severity (odds ratio, 0.81; 95% CI 0.72–0.92), or dementia (odds ratio, 0.65; 95% CI, 0.52–0.81) were less likely to be prescribed. Conclusions—: Prescription of antihypertensive medications poststroke varies between hospitals and according to patient factors including age, sex, stroke severity, and comorbidity profile. Implementation of targeted quality improvement initiatives at local hospitals may help to reduce the variation in prescription observed. Abstract : Supplemental Digital Content is available in the text.